PENGARUH WAKTU FERMENTASI TEMPOYAK TERHADAP SIFAT ORGANOLEPTIK SAMBAL TEMPOYAK - Lindah Anggraini; Lina Widawati (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2015)
Tempoyak a fermented food from durian fruit with a sour taste. Tempoyak made with the addition of salt as much as 1-1.5% into pulp which is then cured for three to seven days at room temperature. This study aims to determine the effect of variations in the level of consumer preferences of the fermentation time in processing tempoyak sauce. The research was conducted three phases, namely fermentation stage tempoyak with treatment fermentation time (3, 5, and 7 days), the processing stage tempoyak sauce, and phase analysis of the level of preference. Results of the analysis conducted on the analysis of the level of preference expressed in tempoyak sauce stated that there was no noticeable difference in tempoyak sauce based parameters tempoyak sauce taste and texture. But there is a noticeable difference in tempoyak sauce based on the parameters of color and flavour tempoyak sauce. From the color parameters, panelists preferred the tempoyak sauce with fermentation time treatment 3 and 5 days. While the parameters of flavour, panellists preferred the tempoyak sauce with fermentation time treatment 5 and 7 days.Keywords: Fermentation, tempoyak, tempoyak sauce